Investigation of Insulation Layers on Additive Manufactured Electrical Steel Laminations in Electric Motors - Ziegler, Marco; Schafer, Paul; Wieprecht, Nico; Franke, Jörg; Kühl, Alexander (IEEE Transactions on Dielectrics and Electrical Insulation, 2023)
In this paper, the insulation properties of printed electrical steel laminations for high-efficiency electric machines are investigated. In contrast to conventionally produced electrical steel laminations made from rolled coil material, additive manufacturing from powder material allows extremely thin and complex near-net-shape geometries with no scrap material. At the same time, the printed electrical steel laminations offer the advantage that no additional cutting steps are required and specific material characteristics are adjustable which enables special machine modifications. To avoid global eddy current paths between the single sheet layers after the stacking process, the laminations must be insulated from each other in order to keep losses low, especially at high operating frequencies. This requires a sufficiently high surface insulation resistance on the sheets. Since the insulation coating cannot be applied continuously during rolling, as in conventional production, alternative approaches for application are required. The investigations characterize and evaluate potential insulation systems for additive manufactured laminations. The printed sheets are analyzed geometrically, electrically and metallurgically at first and characterized for the next process steps. Afterwards, potential insulation systems are analyzed and investigated in practical tests. The coating systems are characterized in terms of application, thickness, electrical and mechanical insulation properties, and options for further processing. This is crucial as the coating needs a sufficient level of adhesion to the substrate and allows successive bonding.
CRIS-Team Scopus Importer:2023-04-14
Keywords: Core losses; Eddy currents; Electric motors; Electrical insulation; Insulation; Lamination; Lamination; Magnetic cores; Magnetic materials; Metals; Soft magnetic materials; Steel; Three-dimensional printing